2014
DOI: 10.1002/mrm.25224
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to detect abnormal relative wall shear stress on the full surface of the thoracic aorta using four-dimensional flow MRI

Abstract: Purpose To compute cohort-averaged wall shear stress (WSS) maps in the thoracic aorta of patients with aortic dilatation or valvular stenosis and to detect abnormal regional WSS. Methods Systolic WSS vectors, estimated from 4D flow MRI data, were calculated along the thoracic aorta lumen in 10 controls, 10 patients with dilated aortas and 10 patients with aortic valve stenosis. 3D segmentations of each aorta were co-registered by group and used to create a cohort-specific aortic geometry. The WSS vectors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 45 publications
4
98
0
Order By: Relevance
“…The 3 patient cohorts (RL‐BAV, RN‐BAV, and TAV‐TAA) were further stratified by those with none, mild, and moderate‐to‐severe AS. For each cohort, a “shared aorta geometry” was created by a previously described rigid registration approach, which maximizes the overlap of all aortic segmentations in the group 12. Next, the systolic 3D WSS data were calculated for each individual patient and then interpolated to the group‐specific shared aorta geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 patient cohorts (RL‐BAV, RN‐BAV, and TAV‐TAA) were further stratified by those with none, mild, and moderate‐to‐severe AS. For each cohort, a “shared aorta geometry” was created by a previously described rigid registration approach, which maximizes the overlap of all aortic segmentations in the group 12. Next, the systolic 3D WSS data were calculated for each individual patient and then interpolated to the group‐specific shared aorta geometry.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have confirmed that the modified hemodynamic environment associated with aortic dilatation and valve abnormalities will cause altered wall shear stress (WSS), a known mechanotransduction stimulus impacting cell function and influencing aortic wall remodeling 12, 13. Furthermore, advances in imaging have enabled the robust use of 4‐dimensional (4D) flow magnetic resonance imaging (MRI), a technique which is capable of measuring 3‐dimensional (3D) blood velocity and WSS in the entire volume of the thoracic aorta 14.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of elevated WSS was expressed as the surface area with elevated WSS as a percentage of the entire surface area of the ascending aorta. Finally, the heat maps were projected on cohort-specific 'shared' geometries [19]. By addition of the heat maps, a 3D incidence map showing regional incidence of elevated velocity and WSS was created [18].…”
Section: Data Analysis -Velocity and Wssmentioning
confidence: 99%
“…In the current study, pre-operative volumetric WSS was used to identify abnormal WSS in individual BAV patients who underwent ascending aortic repair by comparison with an ensemble-average WSS map (24) of healthy volunteers. The aim was to present a large amount of information in an easy to interpret ‘heat map’, capable of delineating regions of abnormal WSS in single-patient BAV cases by comparing them to WSS maps obtained from ensemble averages of healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ascending aortic regions with abnormal WSS were compared to the region of tissue that was resected. Furthermore, ensemble-average WSS maps can be used as P -value maps (24) which visualize and quantify regions of significant, ensemble-averaged WSS differences (for example, to show the average difference of WSS expression in various valve morphology phenotypes).…”
Section: Introductionmentioning
confidence: 99%